STRATEGIES FOR ARTIFICIAL INTELLIGENCE ADOPTION AND ITS IMPACT ON MANAGEMENT PROCESSES (World Conference on Social Sciences, Law and Public Policy, 2026)
This paper delves into the multifaceted strategies for the successful adoption of Artificial Intelligence (AI) within contemporary business environments. It examines the critical factors influencing AI integration, ranging from technological readiness and organizational culture to workforce upskilling and ethical considerations. The research highlights how strategic AI adoption can fundamentally transform existing management processes. This includes improvements in decision-making through data-driven insights, enhanced operational efficiency via automation, and the development of new customer engagement models. Furthermore, the paper explores the challenges organizations face during AI implementation, such as data privacy concerns, potential job displacement, and the need for robust governance frameworks. It provides a comprehensive overview of best practices and methodologies for navigating these complexities, ultimately aiming to equip leaders with the knowledge necessary to harness AI’s full potential.
Keywords: Artificial intelligence, AI adoption, management processes, digital transformation, organizational change, automation, data-driven decision making, workforce upskilling.